Leisure Time of Young People Studying before and During The Covid-19 Pandemic - Agnieszka PAWLUK-SKRZYPEK; Monika JUREWICZ (Communications of International Proceedings, 2022)
The main objective of the study was to analyse how the free time budget is perceived and managed by students before and during the pandemic. The issue seems to be important insofar as in the literature on the subject, the category of leisure time is located at the extreme pole in relation to the category of work/duties. Moreover, due to its location, leisure time has many important functions to fulfil, such as restoring physical and mental strength after work, satisfying entertainment needs, developing interests and talents, or finding one's place in society. Meanwhile, in the pandemic reality, free time has been located in the same place and space as the time reserved for the fulfilment of family, educational or professional duties, and due to numerous restrictions, the possibilities for free use of its forms and benefits have been significantly limited. The authors analyse the category of free time from a temporal perspective by asking about its perception, management, and organisation by young students. The research was carried out using the method of a diagnostic survey, where the technique of a questionnaire created on the Google platform was used.
Keywords: leisure time; studying youth; pandemic